Glucose-insulin-potassium alleviates uterine cramping pain following cesarean delivery: A randomized, controlled trial - Yang, Guiying; Cui, Yu; Bao, Xiaohang; Wu, Zhuoxi; Chen, Qin; Chen, Feng; Liu, Wenjun; Wang, Mingming; Luo, Li; Li, Hong (Frontiers in Surgery, 2023)
Objectives: To explore the effect of glucose-insulin-potassium (GIK) therapy on uterine cramping pain (UCP) following cesarean delivery (CD). Design: Single-center, randomized controlled study. Setting: Second Affiliated Hospital of Army Medical University, Chongqing, China. Participants: A total of 140 women, aged 20–40 years, who underwent CD with a transverse incision were randomly assigned to the GIK (P) or control (C) groups in a 1:1 ratio. Interventions: GIK was intravenously administered to patients in Group P. Patients in Group C received normal saline (NS). After umbilical cord clamping, oxytocin was administered intravenously. The same GIK and NS regimens were administered on postoperative days 1 and 2, followed by oxytocin ten minutes later. Primary and Secondary Outcome Measures: Following oxytocin administration, UCP was assessed using the visual analog scale (VAS), and the maximum VAS score (primary outcome) was recorded. Results: Patients in Group P had significantly lower maximum VAS scores than those in Group C on postoperative days 1 (38.4 ± 21.1 vs. 52.3 ± 20.8, p<0.001) and 2 (10 [0,30] vs. 30.5 [8.75,50], P<0.001). Group P patients also had shorter pain duration on postoperative day 1 (39.6 ± 19.5 min vs. 50.6 ± 18.2 min, p=0.001). Group P patients had a lower incidence of inadequate analgesia of UCP than Group C on days 1 (45.5% vs. 74.2%, p<0.001) and 2 (10.6% vs. 47.0%, p<0.001); the RRs for experiencing inadequate analgesia for UCP postpartum in Group P patients was 0.612 (95% CI: 0.454–0.826, p<0.001) on day 1 and 0.226 (95% CI: 0.107–0.476, P<0.001) on day 2. The absolute risk reduction(ARR) was 28.7%; thus number needed to treat (NNT) was 3 after rounding up.A subgroup analysis demonstrated that Group P patients undergoing repeat CD had lower maximum VAS scores for UCP on both postoperative days 1 and 2. Conclusions: Our findings suggest that GIK can relieve UCP and shorten its duration. Our results provide information to facilitate the development of novel approaches for managing UCP.